Two alien invasive acacias in Italy: Differences and similarities in their flowering and insect visitors. (3rd March 2016) - Giuliani, C.; Giovanetti, M.; Foggi, B.; Mariotti Lippi, M.
Abstract : In Italy, alien acacias have been introduced for ornamental and reforestation purposes, and some species became invasive occupying patches of the Mediterranean landscape. On the Island of Elba (Central Italy), Acacia dealbata and A. pycnantha form dense stands at short distance, showing an impressive massive flowering at the end of the winter/early spring. Our aim was to investigate the behaviour of the two species in relation to the flowering features, from phenology to floral characteristics, and their replay to the observed flower visitors. Differences between the two species emerged on all the parameters considered. A. pycnantha peak of flowering occurred later than A. dealbata and showed larger flower heads (FHs), more flowers/head, stamens/flower and polyads. On A. dealbata, we recorded longer racemes and more FHs/raceme, determining a more flower-dense crown. Even if contacts with flower visitors were generally low on both species, A. dealbata showed a more heterogeneous visitor assemblage. Both acacias species interacted with local generalist pollinators, as bumblebees and honey bees. Flower handling and resource collection strategy by the honey bee indicate a long-term relationship between the bee and the acacias, with bees investing longer time on the larger A. pycnantha flower heads.